(untitled) (Research, Society and Development, 2021)
This article is based in a study of case that craves to analyze which are the impacts in human development, promoted by an Organization of Civil Society – OCS that acts supporting people who are in oncologic treatment in the State of Rio Grande do Sul, as well as, expatiates about the adaptions that were needed to give continuity to the services in Covid-19’s function. It is known that nowadays the Tertiary Sector appears as an option to fill the blanks that the governments leave behind, once that they cannot solve all the social issues. Thus, it is necessary, that voluntary actions, through the OCSs or through other cantles of the tertiary sector sum efforts to make a transformative result in people’s life, ensuring this way, that the people can have access to their rights, putting them in an inclusion space and empowerment, specially about health questions. About the methodologic process, this research was constructed from qualitative nature, explanatory and descriptive, where it was accompanied for about two and a half years the daily life inside the OCS. The study found the importance of this entity in people’s life, once it was noticed how much this support was positive for these families assisted, making them stronger and providing cherish facing the oncologic treatment.